Minimum tillage - Paparella, Antonio; Petsakos, Athanasios; Davis, Kristin E.; Song, Chun (International Food Policy Research Institute, 2025)
Soil tillage represents a key agricultural management practice for crop production, serving multiple purposes. Primarily, it is used to control weeds and increase the soil organic matter mineralization rates, making nutrients more available to plants. Other potential benefits are improved soil aeration and water filtration. However, extensive use of tillage has proven unsustainable for soil maintenance and climate regulation. Deep plowing and other cultivation practices lead to soil degradation by increasing susceptibility to erosion [1], soil runoff [2], and by reducing microbial diversity and activity [3]. Minimum tillage and no-tillage (also known as zero-tillage) address these problems by reducing soil cultivation to a minimum, or entirely avoiding it, thus promoting less disruptive and potentially more sustainable agricultural management. Specifically, no-tillage eliminates traditional plowing practices with the use of direct seeding. To be effective, direct seeding is preceded by other land preparation practices, including chemical or mechanical weed control (e.g., slashing), removal of the previous crop residues, or cover crops to create a mulch layer. Crop residues are retained entirely, or at a suitable level to ensure complete soil coverage. Seeding is then done directly through the mulch layer or through narrow slits for seed placement. Occasionally, direct seeding can be done just before harvesting the previous crop. This practice, known as relay cropping, is used to reduce weed emergence during the period the land would otherwise lie fallow. Finally, direct seeding can be also done jointly with fertilizer and amendment applications. Minimum tillage is also promoted as a method to reduce air pollution, for instance in India, where previously farmers used to burn rice straw but now apply direct seeding on cut crop residues which are spread as mulch.